2017
DOI: 10.17081/eduhum.19.32.2533
|View full text |Cite
|
Sign up to set email alerts
|

Relação Entre O Estado Psicossocial Do Cuidador Informal E O Tempo De Cuidado Dos Idosos Da Região Centro De Portugal

Abstract: O papel desempenhado pela família e cuidadores no tratamento dos idosos é essencial para a promoção e manutenção da sua qualidade de vida, garantindo a sua manutenção do domicílio por um período de tempo mais alargado. Objetivo: Compreender a existência da sobrecarga do cuidador informal e os fatores associados (apoio disponíveis e perfil), bem como estudar o estabelecimento relacional entre o tempo e a sobrecarga. Metodologia: Um questionário de dados sociodemográficos e QASCI (Questionário de Avaliação da So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 2 publications
0
8
0
12
Order By: Relevance
“…Having a kinship relationship is a predictor of burden due to the accumulation of roles. (18,19) The age of the caregiver is positively correlated with the domains of efficacy and control and satisfaction with the role and family, i.e., the older the caregiver, the greater the perceived burden in these aspects. Thus, older caregivers find fewer facilitators to cope with the difficulties resulting from this role and less satisfaction in caring for their relatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a kinship relationship is a predictor of burden due to the accumulation of roles. (18,19) The age of the caregiver is positively correlated with the domains of efficacy and control and satisfaction with the role and family, i.e., the older the caregiver, the greater the perceived burden in these aspects. Thus, older caregivers find fewer facilitators to cope with the difficulties resulting from this role and less satisfaction in caring for their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports other studies in different contexts in Brazil (27,28) and internationally. (19) In Canada, the evaluation of the caregiver burden of stroke survivors revealed that the burden of caring for a dependent person is greater for the perceived time spent than for difficulties in carrying out care activities for the relative. The caregivers perceived most of the tasks as being of mild to moderate difficulty, however, the amount of time spent performing these tasks was perceived as more burdensome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 They are no different from Portugal, where the characteristics of the caregiver profile are young adults, married, cohabitation with the patient, and the reasons for caring are related to the caregiver's duty and emotional connection with the subject. 16 This work showed that, in addition to the issues aforesaid, there is a socioeconomic factor. Most families survive on up to three minimum wages (US$ 792.00), whose health, psychosocial, and functional performance conditions are directly influenced by socioeconomic variables.…”
Section: Discussionmentioning
confidence: 89%
“…26 Others Profile of caregivers of elderly people Martins G, Corrêa L, Caparrol AJS, Santos PTA, Brugnera LM, Gratão ACM authors argue that because the caregivers exert this function for a considerable period of time, positive feelings are awakened about the relationship caregiver-elderly. 27 Therefore, the research contributions meet the importance of studying the differences and similarities between formal and informal caregivers, and of indicating them for their participation along with a social support net, in companionship groups, once enable the change of information about the elderly´s disease, maximizing care already performed, in addition to change of experiences about feelings and expectancies of this public before the task of caring for. 28 Moreover, there is need for the creation and implementation of health public policies addressed to the assistance of these individuals and the creation of a care plan, in order to point out ways of reduction of the generate impact, as well as to provide the increase of the support network to caregivers of dependent elderly people.…”
Section: Profile Of Caregivers Of Elderly Peoplementioning
confidence: 99%